Bisphosphonate-related osteonecrosis of the jaw: An enigma among medical practitioners - Shalini Krishnan; Vijith Shetty; Jayarama Shetty; Gogineni Subhas Babu; T P Rajeev (Indian Journal of Medical and Paediatric Oncology)
Context: Owing to the increasing number of cancer cases, and introduction of newer drugs like bisphosphonates (BP) for the management of metastatic bone disease, complications such as bisphosphonate-related osteonecrosis of the jaw (BRONJ) have come into light. However, several of the treating physicians are not fully aware of this adverse effect. Aim: This study aimed to assess the knowledge and awareness of physicians regarding BRONJ and practices related to bisphosphonate use. Settings and Design: A cross-sectional study conducted among health-care professionals in various medical institutions in Mangalore. Subjects and Methods: A questionnaire was developed to assess the knowledge and awareness of physicians about osteonecrosis of the jaw and practices related to bisphosphonate use, consisting of 21 questions, 12 – knowledge based and 9 – practice based. The questionnaire was validated and distributed among 113 doctors; their responses assigned scores, tabulated and assessed. Statistical Analysis: One-way analysis of variance and Tukey test. Results: More than 50% of the medical professionals had a score <40%, which shows a lack of knowledge about BP and BRONJ. About 45% of the medical professionals in the study group failed to identify the clinical features of BRONJ, and 67.26% were unaware of the risk associated with tooth extractions and oral surgical procedures in the development of the condition. Conclusion: Bisphosphonate-related osteonecrosis is almost exclusively seen in the jaws and hence, the diagnosis usually made by a dental practitioner. Lack of awareness of jaw osteonecrosis among the medical practitioners can result in delay in providing the right treatment.